Trends in adverse perinatal outcomes and associated hospitalisations, emergency department presentations, and healthcare costs from birth to early childhood in the Northern Territory, Australia: A two-decade population-based study. - Tsegaye G Haile; Gavin Pereira; Richard Norman; Gizachew A Tessema (PLOS Global Public Health)
Adverse perinatal outcomes, including preterm birth (PTB), small-for-gestational-age (SGA), and low birthweight (LBW), impact childhood health and impose substantial burdens. This retrospective cohort study included all births in the Northern Territory, Australia, from July 1, 2000, to June 30, 2016, examining trends in these outcomes and related hospitalisations, emergency department (ED) presentations, and healthcare costs through June 30, 2021. Births were linked to hospitalisation, ED, and cost-weight data. Cost, adjusted to June 2024 Australian Dollars (AUD), includes both direct medical and non-medical components. A Generalized Additive Model with a gamma distribution and log link was used to identify cost drivers. A total of 31,183 and 42,174 births were linked to hospitalisations and ED records, respectively. The incidence of PTB increased from 8.1% to 8.7%, while SGA declined from 15.2% to 11.3%. The mean number of hospitalisations by age five increased for children with PTB (1.3 ± 0.7 to 6.9 ± 6.0), and SGA (1.2 ± 0.6 to 8.1 ± 15.1), despite a decline in length of stay. ED presentations also increased for children with PTB (1.3 ± 0.5 to 11.5 ± 10.7), SGA (2.2 ± 1.9 to 12.2 ± 11.5), and LBW (1.2 ± 0.2 to 10.9 ± 8.7). Median five-year hospitalisations cost was AUD 23,848 (IQR: 11,858-44,475) for children with PTB and SGA, compared with AUD 8,668 (IQR: 4,365-17,855) for term non-SGA children. ED cost was AUD 3,108 (IQR: 1,609-7,520) versus AUD 2,058 (IQR: 1,032-4,057), respectively. Costs increased over time for SGA and LBW but declined slightly for PTB. Higher costs than the national average were observed among Indigenous children, those from remote areas, and those with prolonged hospital stays. The healthcare burden associated with adverse perinatal has increased in recent cohorts, particularly among vulnerable groups. Future studies should quantify these burdens across population subgroups to better inform policy.